Principles of object oriented modeling and simulation with Modelica 3.3 : a cyber-physical approach - Fritzson, Peter A., 1952- (Hoboken, New Jersey : John Wiley & Sons Inc., 2015)
Fritzson covers the Modelica language in impressive depth from the basic concepts such as cyber-physical, equation-base, object-oriented, system, model, and simulation, while also incorporating over a hundred exercises and their solutions for a tutorial, easy-to-read experience. The only book with complete Modelica 3.3 coverage Over one hundred exercises and solutions Examines basic concepts such as cyber-physical, equation-based, object-oriented, system, model, and simulation.
3.17 Nested Lookup Procedure in Detail3.18 The Concepts of Type and Subtype; 3.19 Use of Subtyping and Type Compatibility; 3.20 Summary of Type Concepts; 3.21 Summary; 3.22 Literature; 3.23 Exercises; Chapter 4 Inheritance, Modifications, and Generics; 4.1 Inheritance; 4.2 Inheritance through Modification; 4.3 Redeclaration; 4.4 Parameterized Generic Classes; 4.5 Designing a Class to Be Extended; 4.6 Adapting and Extending Libraries by class extends; 4.7 Summary; 4.8 Literature; 4.9 Exercises; Chapter 5 Components, Connectors, and Connections; 5.1 Software Component Models.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Modelica; Modelica; Object-oriented methods (Computer science); Computer simulation; Computer simulation; Modelica; Object-oriented methods (Computer science); Electronic books; Electronic books